Tradisi Tahlilan di Nagari Simpang Kapuak Kecamatan Mungka Kabupaten Lima Puluh Kota dan Nilai-Nilai Pancasila - Akmal, Eko; Moeis, Isnarmi; Dewi, Susi Fitria; Luthfi, Zaky Farid (Journal of Civic Education, 2025)
This study explores the Tahlilan tradition, its core values, and its alignment with Pancasila principles using a qualitative descriptive approach. Data were collected through observations, interviews, and documentation, with analysis following data reduction, presentation, and conclusion verification. Findings reveal that Tahlilan consists of preparations and Tahlil recitations, embodying values such as religiosity, charity, solidarity, mutual cooperation, and justice. These values strongly align with Pancasila, particularly belief in God Almighty, as seen in the religious nature of the ritual. Humanitarian values emerge through social care and assistance, while national unity is reflected in community collaboration and gotong royong. The democratic principle appears in the deliberative selection of Tahlilan leaders, and social justice is evident in equal participation regardless of social status. This study highlights Tahlilan as a living manifestation of Pancasila, reinforcing spiritual solidarity and social harmony in Indonesian society.